Analysis of mental spaces in Persian children stories: A cognitive approach - Reza Kheirabadi; Masumeh Kheirabadi (مطالعات زبانی و بلاغی)
This article aims to study mental spaces in Persian children stories within a cognitive linguistic framework. As a new branch of the linguistics, cognitive linguistics was established in 1970s. In this approach, language is considered as a reflection of thought, and studying language patterns maps conceptualization. Cognitive linguistics is distinguished from the other branches of the discipline by the presupposition that language represents fundamental features and the detailed mapping of human mind. The main purpose of this study is to find mental structures and fundamental concepts on which Persian authors of children books base their stories. To conduct the research, data was gathered through library resources and, from a corpus of fifty children stories, five stories were accidentally selected and analyzed descriptively within Gilles Fauconnier’s (1997) mental spaces framework. Findings show that base space in the selected stories is constructed on the concept of “Loneliness” and presupposes that being trapped in loneliness is a problem with endless pain and sorrow. In other words, loneliness has been represented as a negative concept so that the next mental spaces be distanced from it. Stereotypically, fictional characters face this problem involuntarily, try to get out of it, and finally gain victory. The works under study in this research contain the message of collectivism and philanthropy, and the created mental spaces lead children audience to a sense of empowerment in social relations. The findings of this study can be useful both for authors and editors of children stories.